A 2D/1D heterojunction nanocomposite built from polymeric carbon nitride and MIL-88A(Fe) derived α-Fe2O3 for enhanced photocatalytic degradation of rhodamine B. (21st April 2022) - Viswanathan, Vandana P.; Nayarassery, Adarsh N.; Xavier, Marilyn Mary; Mathew, Suresh
Abstract : 2D/1D heterojunction α-Fe2 O3 /C3 N4  photocatalysts containing α-Fe2 O3  microrods and polymeric carbon nitride flakes are synthesised through the calcination of Fe-based metal-organic frameworks and boost the visible light photocatalytic degradation of rhodamine B. Abstract : Fabricating heterojunction catalysts is a promising strategy for enhancing the performance of heterogeneous photocatalytic reactions. Based on the nontoxicity and low cost of photocatalyst, we synthesized two dimensional/one dimensional (2D/1D) heterojunction photocatalysts, namely α-Fe2 O3 /C3 N4 - x % (FC- x = 4, 8, and 12) containing α-Fe2 O3 microrods and polymeric carbon nitride (C3 N4 ) flakes through the calcination of Fe-based metal-organic framework (MIL-88A(Fe)) with C3 N4 for boosting visible light photocatalytic degradation of rhodamine B (RhB). The synthesized composite materials are characterized by FTIR, PXRD, UVDRS, PL, FESEM, TEM, BET and TG/GC/MS analysis. Due to the 2D/ID heterojunction formation between C3 N4 and α-Fe2 O3, the band gap of α-Fe2 O3 /C3 N4 composite (FC-8) is reduced to 2.05 eV compared to C3 N4 and α-Fe2 O3 . The hybrid system α-Fe2 O3 /C3 N4 -8% (FC-8) showed excellent photocatalytic activity for the degradation of RhB under sunlight. The hybrid FC-8 shows 92% degradation of RhB in 60 min under sunlight. A possible Z-scheme mechanism for the enhanced photocatalytic activity of the FC-8 composite is also proposed. More importantly, the fabricated 2D/1D heterojunction between α-Fe2 O3 and C3 N4 efficiently speeds up the transfer and separation of photoinduced charge carriers, which is beneficial for photocatalytic activity. Trapping experiments revealed that superoxide radicals are the prime radicals responsible for the degradation of RhB. The hybrid system FC-8 showed high recyclability and chemical stability.